"Is Our Name Remembered?": Writing the History of Iranian Constitutionalism as if Women and Gender Mattered - Najmabadi, Afsaneh (جماعة, 1999)
Through the retrieval of the story of the daughters of Quchan, Afsaneh Najmabadi describes the project of modernity in early twentiethcentury Iran as a continuous and a discursive one. This event which played a desicive role in the Constitutional Revolution was the starting point for a dynamic process that formulated modern judicial, political, constitutional, institutional and national practices and values. The Iranian project of modernity reinforced certain deeply embedded beliefs and practices about gender and the place of women in society. In this sense the modern discourse in the Iranian context emerges as a series of movements within the regime of pre-modernity. Through the story of the daughters of Quchan Najmabadi also points to the historiographical practices that excluded women from the Iranian collective memory and national narrative, even though this story was a formative one and of major importance in the history of the Constitutional Revolution. The study highlights the masculinity of the Iranian national narrative and suggests that the incorporation of both gendered and national discourses can bring out a more balanced representation of reality as well as an alternative to the history writing on modernity.